2016
DOI: 10.1093/conphys/cow009
|View full text |Cite
|
Sign up to set email alerts
|

Are global warming and ocean acidification conspiring against marine ectotherms? A meta-analysis of the respiratory effects of elevated temperature, high CO2and their interaction

Abstract: The changing climate prompts the need to study and ultimately predict the outcome for marine ectothermic animals. An analysis of the effects on respiratory performance of rising temperature, carbon dioxide, and their interaction, reveals diverse responses and a trend for additive and antagonistic rather than synergistic interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
179
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(196 citation statements)
references
References 257 publications
(417 reference statements)
10
179
1
Order By: Relevance
“…Thus, this inherent plasticity precludes broad generalizations based on single, short-term experiments, but understanding such plasticity is fundamental in assigning potential risks to ongoing climate change [83,92]. Highly variable CO 2 × temperature responses are common across taxonomic groups [90,93], thus experimental replication and inter-experiment statistical comparisons are necessary for robust evaluations of climate sensitivities in marine organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this inherent plasticity precludes broad generalizations based on single, short-term experiments, but understanding such plasticity is fundamental in assigning potential risks to ongoing climate change [83,92]. Highly variable CO 2 × temperature responses are common across taxonomic groups [90,93], thus experimental replication and inter-experiment statistical comparisons are necessary for robust evaluations of climate sensitivities in marine organisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have found discrepancies in this assumption where growth optima did not correlate with the highest AS (Gräns et al, 2014), and where AS continued to increase up to near-lethal temperatures, while the fish behaviourally preferred colder waters (Norin et al, 2014). Furthermore, a recent review found that fish species do not always have a clear thermal optimum in AS (Lefevre, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are also a range of extrinsic factors that have profound effects on metabolism and aerobic scope in ecotherms. In response to an increase in temperature, for example, SMR and MMR generally increase, with at least some species displaying a decrease in AAS past a species-specific optimum (Farrell 2016;Lefevre 2016). This pattern is often due to a decrease in MMR beyond this point, though not all species display this response and instead reach lethal temperatures before MMR begins to decline (Jutfelt et al 2018;Lefevre 2016;Nati et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In response to an increase in temperature, for example, SMR and MMR generally increase, with at least some species displaying a decrease in AAS past a species-specific optimum (Farrell 2016;Lefevre 2016). This pattern is often due to a decrease in MMR beyond this point, though not all species display this response and instead reach lethal temperatures before MMR begins to decline (Jutfelt et al 2018;Lefevre 2016;Nati et al 2016). Again, however, the exact interpretation of how aerobic scope is affected by temperature is strongly dependent on whether AAS or FAS is used to represent aerobic scope (Clark et al 2013).…”
Section: Introductionmentioning
confidence: 99%